"Girls Have More of an Educational Brain": A Qualitative Exploration of the Gender Gap in Educational Attainment Among Black Bermudian Adolescents. (May 2015) - Jethwani, Monique M.
Although Black boys throughout the African diaspora are dropping out of high school in alarming rates, little is known about how educational identity and attainment is shaped by the intersection of race and gender in the high school environment. Utilizing an ecological and intersectionality theoretical lens, this study draws on data gleaned from semistructured interviews with Black male and female adolescents in their first year at a public high school in Bermuda ( N = 35, mean age = 14.3). Findings indicated that the girls committed twice as many disciplinary infractions as the boys. However, girls' disciplinary problems were less likely to interfere with their academic performance because they were perceived, by both boys and girls, to be more educationally focused, better behaved, and they were more likely to seek out social-emotional support when needed. This study contributes to our understanding of the higher drop-out rates among men of African descent and points to the important role that gender stereotypes and school-based adults play in determining educational identity and attainment.